2015
DOI: 10.1016/j.sjbs.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of circulating biochemical markers and antioxidative status in acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) patients

Abstract: Various circulating biochemical markers are indicators of pathological state in leukemia and its subtypes. Increased oxidative stress and decreased antioxidant factors portray clear image associated with malignancies during subtypes of leukemia. In this research work we investigated the inter-relationship among the subtypes of leukemia with circulating biochemical markers and oxidative stress in the Pakistani population. This research work was conducted on a total number of 70 subjects in which 20 were control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
7
26
0
1
Order By: Relevance
“…In current study it was found that the mean serum aspartate transaminase (AST) level before starting chemotherapy in acute leukemia patients was 38.00 ± 7.34 U/L. This observation was consistent with previous studies as reported that elevated serum aspartate transaminase (AST) is common at initial presentation of acute leukemia due to hepatic injury from leukemic infiltrates [7] [21].…”
Section: Discussionsupporting
confidence: 91%
“…In current study it was found that the mean serum aspartate transaminase (AST) level before starting chemotherapy in acute leukemia patients was 38.00 ± 7.34 U/L. This observation was consistent with previous studies as reported that elevated serum aspartate transaminase (AST) is common at initial presentation of acute leukemia due to hepatic injury from leukemic infiltrates [7] [21].…”
Section: Discussionsupporting
confidence: 91%
“…The result in tables (3) and (4) showed that there was a significant decrease (p≤0.05) for Calcium levels in CSF of patients with acute lymphoblastic leukemia for both sex and in all age group our result was in agreement with previous reports which showed a significant decrease in Calcium levels in serum of acute and chronic leukemia patients [41,42] Ca +² concentrations is also required for efficient CTL and NK cell function and thus for killing their targets [15] Mg is a chemical gatekeeper, so Ca+ entry to nervous cell increases due to Mg deficiency and finally causes overstimulation, spasm, and convulsion [10] the result also showed that the level of calcium in male was higher than female and this was in agreement with. [43] …”
Section: -Calciumsupporting
confidence: 91%
“…The result in tables (3) and (4) showed that there was a significant increase (p≤0.05) for Potassium levels in CSF of patients with acute lymphoblastic leukemia for both sex and in all age group the highest level of potassium was recorded in male with the age of (11-15) years our result was in agreement with previous reports which showed a significant increase in Potassium levels in serum of acute and chronic leukemia patients [42] the increased levels of potassium may be due to the defect in Voltage-gated potassium channels (VGKCs) which represent a group of tetrameric signaling proteins with several functions, including modulation of neuronal excitability and neurotransmitter release. Moreover, VGKCs give a key contribution to the generation of the action potential.…”
Section: -Potassiumsupporting
confidence: 91%
“…To determine the capability of organs functioning, biochemical parameters were taken in concern. All the biological parameters including hematology and body salts studied were found to be associated with ALL as also indicated in previous study [25,26]. The association between the allelic frequency and the study groups, differentiated into cases and controls was evaluated by crosstabs.…”
Section: Discussionsupporting
confidence: 55%